“Efecto de hormonas vegetales y micronutrientes en el llenado de la mazorca de maíz (zea mays) en sauce-San Martín” - Medina García, Gerardo (2003)
· 1n order to increasing the yield and productivity of the corn yellow hard low conditions of tropical humid forest, it was opted to carry out the present investigation work where was evaluated the effect of the application of vegetable hormones and micronutrients (boron and molybdenum) in the one filled of the ear of corn, comparing with a witness and to demonstrate that application ( dose) they are those but favorable 1 lower these conditions to produce high yields. The work was executed in the district of Sallow, county and region from San Martín to 52 Km. of the city of Tarapoto. the objectives of this work were to evaluate the alone applied effect of vegetable hormones and in mixture with micronutrients (8 and Mo), the most appropriate dose for the one filled of the ear of corn and to determine the treatment that produces high yields and to determine the relationship cost-benefit of the different treatments. The Design of Blocks was used Randomizado completely (DBCR) with 6 treatments and 4 repetitions. The yields obtained as for the applications are: T1 = 5 230 Kg/ha (witness) T2 = 6 250 Kg/ha (STIMULA TE) T3 = 6 299 Kg/ha (X - CYTE) T4 = 6 615 Kg/ha (STIMULATE + NITRATE BALANCER) T5 = 6 355 Kg/ha (X-CYTE + NITRA TE BALENCER) T6 = 6 793 Kg/ha (NITRA TE BALANCER) Being differs significant among treatments, of those which the micronutrients application . . . ' . B and Mo (Nitrate balancer) to dose of 4 l/ha, it occupied the first place reaching bigger positiva value in relationship cost benefit of 83.26% of the cost in the beneficent one indicating a net value of earnings of 568.28 new suns that is equal to 16.74%.